VD_FINDINFO Jug / 2014 / 271 vom 16. Mai 2014 - VD Tribunal cantonal (2014)
PARTIE CIVILE, CONDITION DE RECEVABILITÉ, INDEMNITÉ POUR DÉTENTION | 118 CPP (CH), 123 CPP (CH), 431 CPP (CH), 448 al. 1 CPP (CH)